(untitled) (Scientific journal of the Fergana State University, 2026)
This article presents methods of solving problems in molecular physics using digital technologies. In particular, it describes the application of the Python programming language for modeling complex processes in molecular physics, as well as for creating various graphics and visualizations. Moreover, the paper discusses algorithms for solving physical problems, approaches to implementing them through software, and the possibilities of applying these methods in the educational process.